The porosity, microstructure, and hardness of Al-Mg composites reinforced with micro particle SiC/Al2O3 produced using powder metallurgy - Tosun, Gul; Kurt, Mehmet (Elsevier Sci Ltd, 2019)
In this study, Al-Mg metal matrix composite (MMC) materials reinforced with micro-sized SiC, Al2O3 particles were manufactured using powder metallurgy. SiC and Al2O3 particles with 1 pm size were added to the Al-Mg matrix at different volume ratios (15-30%). A mixture of Al, Mg, reinforcement (SiC, Al2O3) powders was mixed at a speed of 16 rpm over a 24 h-time period for a homogeneous dispersion. The mixed powders were pressed at 300 and 600 MPa. Composite materials produced at different pressures were sintered under for 30, 60, 90 min and at 300, 400, 500 degrees C and allowed to cool in the furnace. The microhardness, porosity, microstructure of Al-Mg/SiC and Al-Mg/Al2O3 composites were investigated and characterized. The highest porosity ratio for all test conditions was measured as being 17% in the Al-Mg composite reinforced with 15% SiC produced at 300 MPa and 400 degrees C for 90 min. The lowest porosity ratio was measured as being 5.4% in the Al-Mg composite reinforced with 15% SiC produced at 600 MPa and 500 degrees C for 90 min. In their microstructure studies, a generally homogeneous microstructure was observed.
Keywords: Al-Mg composite; Porosity; Microstructure; Microhardness